Using the TikTok App to Publish Your Love Imperfections Works through the “Love Imperfections Campaign” - Yohana Putri Damayanti Adi Pangestu; Daniel Pernandes; Maria Yuli Indrawati; Maria Lusiana Prihatin (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The COVID-19 pandemic required every person to stay at home and made them look for entertainment. Social media such as TikTok become one of the forms of entertainment that are easy to reach along with the development of technology. TikTok users in Indonesia as of June 2020 reached 30.7 million users. The writing of this scientific work aims at how much influence the Love Imperfections campaign has on TikTok users. This research aimed to see how far the love imperfections campaign influenced TikTok users. The subject of this research was early adolescence divided into the small scope and large scope. The method was research and development. Data was collected through Google Form to small and large scope. The results of the experiment showed that quite a lot of participants felt insecure in themselves with different problems and backgrounds, then also the results on a large scope showed that the average participant felt that the Love Imperfections campaign was very useful, interesting, good, and informative. Then participants want this Love Imperfections campaign to continue to be developed and continued.